PREVALENCE AND ASSOCIATED FACTORS OF ANEMIA AMONG PREGNANT WOMEN AT SANGKRAH COMMUNITY HEALTH CENTER IN SURAKARTA, CENTRAL JAVA: A CROSS-SECTIONAL STUDY - Emma Anastya Puriastuti; Nur Anisah Rahmawati; Nina Rini Suprobo (Universitas Airlangga, 2026)
Pregnancy complications are often associated with anemia, which remains a critical public health problem, particularly in developing countries. Anemia during pregnancy increases the risk of adverse maternal and fetal outcomes, yet effective prevention remains a challenge. This study aimed to explore the prevalence and associated factors of anemia among pregnant women at the Sangkrah Community Health Center in Surakarta, Central Java, Indonesia. This cross-sectional study was conducted in 2025 and involved 96 pregnant women attending antenatal care, selected via purposive sampling. Data were collected using questionnaires and maternal and child health record books, covering sociodemographic, obstetric, and social-environmental factors. Data analysis was performed using descriptive and bivariate statistical tests. The results showed that the prevalence of anemia among pregnant women is 12.5%. Factors significantly associated with anemia were parity, abortion experience, number of living children, and history of blood transfusion (p<0.05). Conversely, other factors such as age, education, occupation, trimester, pregnancy spacing, history of previous births, previous birth complications, planned pregnancy, chronic diseases before pregnancy, drug allergies, Body Mass Indeks (BMI), drug consumption, history of relapse, family support, distance to health facilities, family reminders on supplement adherence, regular exercise and pregnancy information-seeking were significantly associated (p>0.05). These findings highlight the importance of monitoring maternal obstetric history and prior medical conditions as part of anemia prevention efforts during pregnancy. Strengthening antenatal care services and providing targeted Information, Education, and Communication (IEC) at the community health center level are essential to reduce the risk of anemia among pregnant women.